The immunological characteristics and probiotic function of recombinant Bacillus subtilis spore expressing Clonorchis sinensis cysteine protease. Issue 1 (December 2016) - Tang, Zeli; Shang, Mei; Chen, Tingjin; Ren, Pengli; Sun, Hengchang; Qu, Hongling; Lin, Zhipeng; Zhou, Lina; Yu, Jinyun; Jiang, Hongye; Zhou, Xinyi; Li, Xuerong; et al.
Abstract Background Clonorchiasis, a food-borne zoonosis, is caused byClonorchis sinensis . The intestinal tract and bile ducts are crucial places forC. sinensis metacercariae to develop into adult worms. The endospore ofBacillus subtilis is an ideal oral immunization vehicle for delivery of heterologous antigens to intestine. Cysteine protease ofC. sinensis (Cs CP) is an endogenous key component in the excystment of metacercariae and other physiological or pathological processes. Methods We constructed a fusion gene of CotC (a coat protein)-Cs CP and obtainedB. subtilis spores with recombinant plasmid of pEB03-CotC-Cs CP (B.s -CotC-Cs CP). CotC-Cs CP expressed on spores' surface was detected by Western blotting and immunofluorescence. Immunological characteristics of recombinant spore coat protein were evaluated in a mouse model. The levels ofCs CP-specific antibodies were detected by ELISA. Effects of recombinant spores on mouse intestine were evaluated by histological staining. The activities of biochemical enzymes in serum were assayed by microplate. Liver sections of infected mice were evaluated by Ishak score after Masson's trichrome. Results TheB.s -CotC-Cs CP spores displayedCs CP on their coat. Specific IgG and isotypes were significantly induced by coat proteins ofB.s -CotC-Cs CP spores after subcutaneous immunization. IgA levels in intestinal mucus and bile ofB.s -CotC-Cs CP orally treated mice significantly increased. Additionally, more IgA-secreting cells were observed in enteraden andlamina propria regions of the mouse jejunum, and an increased amount of acidic mucins in intestines were also observed. There were no significant differences in enzyme levels of serum among groups. No inflammatory injury was observed in the intestinal tissues of each group. The degree of liver fibrosis was significantly reduced after oral immunization withB.s -CotC-Cs CP spores. Conclusions Bacillus subtilis spores maintained the original excellent immunogenicity ofCs CP expressed on their surface. Both local and systemic specific immune responses were elicited by oral administration ofB.s -CotC-Cs CP spores. The spores effectively promoted intestinal health by inducing secretion of acidic mucins, with no other side effects to the liver or intestine. Oral administration of spores expressingCs CP could provide effective protection againstC. sinensis . This study may be a cornerstone for development of antiparasitic agents or vaccines against clonorchiasis based onB. subtilis spore expressingCs CP on the surface.